Examining Plausibility of Self-Reported Energy Intake Data: Considerations for Method Selection - Banna, Jinan C.; McCrory, Megan A.; Fialkowski, Marie Kainoa; Boushey, Carol (Frontiers in Nutrition, 2017)
Self-reported dietary intake data contain valuable information and have long been used in the development of nutrition programs and policy. Some degree of measurement error is always present in such data. Biological plausibility, assessed by determining whether self-reported energy intake (rEI) reflects physiological status and physical activity level, must be examined and accounted for before drawing conclusions about intake. Methods that may be used to account for plausibility of rEI include crude methods such as excluding participants reporting EIs at the extremes of a range of intake and individualized methods such as statistical adjustment and applying cut-offs that account for the errors associated with within-participant variation in EI and total energy expenditure (TEE). These approaches allow researchers to determine how accounting for under-and overreporting affects study results and to appropriately address misreporting in drawing conclusions with data collected and in interpreting reported research. In selecting a procedure to assess and account for plausibility of intake, there are a number of key considerations, such as resources available, the dietary-report instrument, as well as the advantages and disadvantages of each method. While additional studies are warranted to recommend one procedure as superior to another, researchers should apply one of the available methods to address the issue of implausible rEI. If no method is applied, then at minimum, mean TEE or rEI/TEE should be reported to allow readers to ascertain the degree of misreporting at a gross level and better interpret the data and results provided.